Revealing the Students’ Needs, Treatments, and Perspectives towards TOEFL Difficulties - Sulastri; Homsatun Nafiah; Juni Hartiwi; Nia Sari Nastiti (Global Expert: Jurnal Bahasa dan Sastra, 2026)
Many universities in Indonesia facilitate their students in gaining knowledge and a better understanding of TOEFL. Similarly, Satu Nusa Lampung University implements a Community Service Program to introduce the strategies, tips, and tricks in answering TOEFL sections. The objectives of this research are to identify the students’ initial ability in TOEFL before the training program and to analyse the influence of the training program on the students’ scores; further, the researchers also want to know the most difficult type of TOEFL section based on the students’ perspective. This research applied a mixed-methods approach, integrating both quantitative and qualitative methods to obtain a comprehensive understanding of the research problems. The researchers used TOEFL tests and a semi-structured interview guide as the instruments of this research. From the results, it is known that most students have difficulty answering Listening questions before the training program; therefore, their Listening score is the lowest of all sections. Besides, the students’ score in all of the TOEFL sections after joining the training program increases which means that there is an influence of the training program on the students’ scores in TOEFL. The result also found that, according to students’ perspective, Listening is the most difficult section compared to others. This research contributes to a deeper understanding of the students’ needs related to their ability in answering TOEFL questions and offers insight about the most challenging TOEFL section for students. Keywords: Difficulties, Perspective, TOEFL, Training program